2021
DOI: 10.3390/cancers13030411
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA H19-Derived MicroRNA-675 Promotes Liver Necroptosis by Targeting FADD

Abstract: The H19-derived microRNA-675 (miR-675) has been implicated as both tumor promoter and tumor suppressor and also plays a role in liver inflammation. We found that miR-675 promotes cell death in human hepatocellular carcinoma (HCC) cell lines. We show that Fas-associated protein with death domain (FADD), a mediator of apoptotic cell death signaling, is downregulated by miR-675 and a negative correlation exists between miR-675 and FADD expression in mouse models of HCC (p = 0.014) as well as in human samples (p =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 44 publications
0
31
0
1
Order By: Relevance
“…表 1 参与肿瘤细胞程序性死亡的lncRNAs NLRP3, IL-1β, IL-18, caspase-1/4/5/11 gasdermin [3,23,24] ATG, ULK1, LC3, Beclin1, p62 [25,26] GPX4, NRF2, p53, xCT [27,28] RIP1, RIP3, MLKL [29] 重要肿瘤相关 lncRNAs HOTAIR [11,12] , GAS5 [14] , lincRNA-p21 [30,31] , RoR [32] , PVT1 [33,34] , NEAT1 [35] , MEG3 [36,37] , MALAT1 [38,39] , TUG1 [40] HOTTIP [41] , XIST [42] , NEAT1 [43,44] , GAS5 [17] , MEG3 [45] , SNHG7 [46] , ADAMTS9-AS2 [47] , LINC00958 [48] GAS5 [49] , EGOT [50] , PTENP1 [51] , CASC9 [52] LINC00336 [53] , OIP5-AS1 [54] , P53RRA [55] , LINC00618 [56] , MT1DP [57] , GABPB1-AS1 [58] H19 [59] , Linc00176 [60] 李铮铮等: 长链非编码RNAs在肿瘤细胞死亡中的作用 活性 [36,37] . LncRNA MALAT1则通过结合DBC1蛋白,…”
Section: Lncrnas与凋亡mentioning
confidence: 99%
See 1 more Smart Citation
“…表 1 参与肿瘤细胞程序性死亡的lncRNAs NLRP3, IL-1β, IL-18, caspase-1/4/5/11 gasdermin [3,23,24] ATG, ULK1, LC3, Beclin1, p62 [25,26] GPX4, NRF2, p53, xCT [27,28] RIP1, RIP3, MLKL [29] 重要肿瘤相关 lncRNAs HOTAIR [11,12] , GAS5 [14] , lincRNA-p21 [30,31] , RoR [32] , PVT1 [33,34] , NEAT1 [35] , MEG3 [36,37] , MALAT1 [38,39] , TUG1 [40] HOTTIP [41] , XIST [42] , NEAT1 [43,44] , GAS5 [17] , MEG3 [45] , SNHG7 [46] , ADAMTS9-AS2 [47] , LINC00958 [48] GAS5 [49] , EGOT [50] , PTENP1 [51] , CASC9 [52] LINC00336 [53] , OIP5-AS1 [54] , P53RRA [55] , LINC00618 [56] , MT1DP [57] , GABPB1-AS1 [58] H19 [59] , Linc00176 [60] 李铮铮等: 长链非编码RNAs在肿瘤细胞死亡中的作用 活性 [36,37] . LncRNA MALAT1则通过结合DBC1蛋白,…”
Section: Lncrnas与凋亡mentioning
confidence: 99%
“…目前, 关于lncRNAs参与肿瘤细胞坏死性凋亡的 报道为数不多, 这也提示需要继续深入探索这种死亡 方式. LncRNA H19来源的miR-675, 被报道能上调p-MLKL和RIP3的水平, 同时抑制FADD, cleaved-caspase-8, cleaved-caspase-3的表达, 诱导肝癌细胞发生 坏死性凋亡 [59] . 关于肝癌的另一项研究发现了一种由 c-Myc激活的新的lncRNA Linc00176, 它作为分子海 绵吸附肿瘤抑制miRNAs(miR-9和miR-185)来调控 200多个基因的表达; 当Linc00176表达下调时, 这些 miRNAs得以释放, 导致细胞周期紊乱和坏死性凋亡 的激活 [60] .…”
Section: Lncrnas与铁死亡unclassified
“…Presently, literature is scarce regarding necroptosis-associated lncRNAs. In a related investigation, Harari-Steinfeld et al [ 32 ] highlighted that lncRNA H19-derived miR-675 promoted human hepatocellular carcinoma cell necroptosis in response to inflammation symptoms by targeting Fas-linked protein with death domain. One recent study revealed that the tumor suppressor p53 upregulates lncRNA TRINGS in a direct manner during glucose starvation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, downregulation of lncRNA growth arrest-specific 5 (GAS5) in HCC promotes proliferation and drug resistance through the decrease of phosphatase and tensin homolog (PTEN) expression ( Wang et al, 2020 ). lncRNA small nucleolar RNA host gene 3 (SNHG3) induces epithelial–mesenchymal transition (EMT) and sorafenib resistance by regulating the miR-128/cluster of differentiation 151 (CD151) pathway in HCC ( Zhang et al, 2019 ), having the potential to affect necroptosis through different pathways such as H19-derived miR-675 targeting FAS-associated death domain protein (FADD) ( Harari-Steinfeld et al, 2021 ). In addition, lncRNAs can protect tumor cells from necroptosis by suppressing the expression of some related proteins ( Tao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%